A Nation of Poets and Thinkers' - Less So with Eastern Enlargement? Austria and Germany - Dalia Marin (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
Many people in the European Union fear that Eastern Enlargement will lead to major job losses. More recently, these fears about job losses have extended to high skill labor and IT jobs. The paper examines with new firm level data whether these fears are justified for the two neighboring countries of Eastern Enlargement Austria and Germany. I find that Eastern Enlargement leads to surprising small job losses, because jobs in Eastern Europe do not compete with jobs in Austria and Germany. Low cost jobs of affiliates in Eastern Europe help Austrian and German firms to stay competitive in an increasingly competitive environment. However, I also find that multinational firms in Austria and Germany are outsourcing the most skill intensive activities to Eastern Europe taking advantage of cheap abundant skilled labor in Eastern Europe. I find that the firms' outsourcing activities to Eastern Europe are a response to a human capital scarcity in Austria and Germany which has become particularly severe in the 1990s. Corporations' outsourcing of skill intensive firm activity to Eastern Europe has helped to ease the human capital crisis in both countries. I find that high skilled jobs transferred to Eastern Europe account for 10 percent of Germany's and 48 percent of Austria's supply of university graduates in the 1990s. I then discuss what can be done to address the skill exodus to Eastern Europe. I show that R&D subsidies do not work in economies with a skill crisis and I suggest to liberalize the movement of high skill labor with Eastern Enlargement.
urn:nbn:de:bvb:19-epub-13474-1
Keywords: F21; F23; J24; J31; L24; O3; P33; 330; human capital; intra-firm trade; multinationals and jobs; out-sourcing to Eastern Europe; R&D policy